Leadership characteristics and behavior of school administrators in selected districts, Division of Quezon school : a study - Atendido, Gloria R. (Manila : National University, 2005)
This study attempted to study the leadership characteristics and behavior of school administrators of selected districts in Division of Quezon in school year 2004-2005.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- List of Figures -- Chapter 1: The Problem and its Background -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Letter of Request -- Questionnaire -- Curriculum Vitae .
Research Method: Descriptive Method.
Includes bibliographical references.